Optimal approximation, simulation and analog realization of the fundamental fractional order transfer function - Djouambi, Abdelbaki; Charef, Abdelfettah; Besançon, Alina Voda (Zielona Góra: Uniwersytet Zielonogórski)
This paper provides an optimal approximation of the fundamental linear fractional order transfer function using a distribution of the relaxation time function. Simple methods, useful in systems and control theories, which can be used to approximate the irrational transfer function of a class of fractional systems for a given frequency band by a rational function are presented.
Keywords: fractional systems; approximation; simulation and distribution of the relaxation times function